Spatial Modelling Untuk Analisis Ketimpangan Akses Transportasi Perkotaan di Bandar Lampung - Iman Ceria Invokafit; Prayogi, Prayogi; Valeri Destia Putri Pratama; Hidayati, Solikhah Retno (ReTII, 2025)
Modern urban areas face complex challenges related to the interconnection between transportation systems, land use, and the quality of accessibility for their residents. Accessibility, which refers to an individual’s ability to reach activities, services, jobs, or facilities within a certain time and cost limit, becomes an important indicator in urban and regional planning because it reflects how urban space facilitates mobility, social and economic interactions, as well as spatio-temporal inclusion. For instance, in the context of developing cities, studies have shown that inequalities in transportation accessibility can reinforce spatial-social disparities and reduce mobility efficiency for residents (Giannotti et al., 2021) [1]. In line with this, sustainable urban development policies increasingly emphasize that improving vehicle mobility is not only important, but also how transportation systems and road networks support equitable and efficient accessibility. Therefore, this study will conduct spatial modeling to identify and analyze transportation accessibility inequalities in the city of Bandar Lampung, with the aim of providing recommendations for more equitable urban and regional planning that supports mobility and urban growth.